ART THERAPY BENCANA SEBAGAI UPAYA PENANGANAN TRAUMA ANAK PASCA GEMPA LOMBOK - Fitri Aulia (Bahasa Indonesia, 2019)
This activity aims to treat psychologically the victims of earthquakes in Lombok which occurred in mid-2018. The targets were chosen based on the location of the earthquake affected in severe status, namely in SDN 1 Sembalun. Children become important victims to be given care so as not to experience prolonged trauma. Art Therapy is the right method to be applied to children. The disaster art therapy carried out in this activity is, (1) Free drawing on the clouds. (2) Drawing feelings. (3) Free writing techniques. (4) Free storytelling techniques. Based on the results of the evaluation of activities it was found that children became calmer. It is expected that through this activity elementary teachers are able to have skills in overcoming students' anxiety and trauma in the event of aftershocks. First, post-earthquake trauma in children is easy to return to if aftershocks occur. Secondly, a continuous psychological assistance program is needed from all teachers and the community. Third, it is necessary to improve physical facilities and play environments in the community and schools.